The Main Directions of Improving the Personnel Management of the Hotel Industry in the Field of Tourism - Egamberdiyeva Sevara Abduxolikovna (Research Parks Publishers, 2022)
The article addressed the issues of the main areas of improvement of the personnel management of the hotel industry in the innovative development of the tourism industry were considered. In this instance, the author provided the definition of the management decision, the management decision in the tourism sector, and the management decision in the hotel industry as a result of the research. These actions were taken in the manager's order to make a decision intended to increase the efficiency of the management sector and ensure its implementation.